(untitled) (Global Journal of Science Frontier Research, 2020)
Climate change refers to a significant change in the measures of climate, such as in temperature, rainfall, snow, or wind patterns lasting for decades or longer. The Earth’s climate has changed many times during the planet’s history. It is a real and urgent challenge that is already affecting people and the environment worldwide. This review article focuses on identify different causes of the climate change. Understanding the causes of climate change helps to raise public awareness, theoretical studies, feedback processes and model simulations. It helps to share the information for experts and policy makers about applicable and beneficial adaptation and mitigation strategies. Hence, this article is produced through referring various secondary data sources and desktop data analysis. Accordingly, many factor both natural and anthropogenic activities are drivers of climate change. But, various studies indicated that most of the causes of climate change in the current era is the result of human activities.